The Relationships Between Leadership and Corporate Social Responsibility: Systematic Literature Review - Czerniachowicz, Barbara; Lis, Andrzej; Wieczorek-Szymańska, Anna (Journal of Corporate Responsibility and Leadership, 2018)
The issues of leadership and corporate social respon-sibility have been thoroughly investigated and widely discussed in the literature but these two concepts have been seldom studied together. The aim of the paper is to identify the key research prob-lems and approaches related to the relationships between leader-ship and CSR manifested in quality publications. The systematic literature survey methodology is applied to identify and analyse key publications in the field. The research sample includes the quality papers retrieved from the Web of Science Core Collec-tion database. The paper discusses main research problems and issues related to the study of relationships between leadership and CSR, research approaches, methods and study contexts. Finally, the paper provides recommendations for further studies related to relationships between the concepts of leadership and corporate social responsibility.